Testing the effects of the GLP-1 receptor agonist exenatide on cocaine self-administration and subjective responses in humans with cocaine use disorder - Angarita, Gustavo A.; Matuskey, David; Pittman, Brian; Costeines, Jessica L.; Potenza, Marc N.; Jastreboff, Ania M.; Schmidt, Heath D.; Malison, Robert T. (Drug and alcohol dependence, 2021)
•The effects of a GLP-1 agonist (exenatide) on behavioral and subjective effects of cocaine were examined.•All subjects participated in a self-regulated cocaine self-administration paradigm.•Exenatide had no effect on administration and subjective effects of cocaine.•Both exenatide and cocaine decreased levels of GLP-1 and insulin. Preclinical rodent studies have demonstrated reduced cocaine taking after administration of glucagon-like peptide 1 (GLP-1) analogues. We investigated effects of a GLP-1 analogue (exenatide) on behavioral and subjective effects of cocaine in individuals with cocaine use disorder (CUD). Non-treatment-seeking CUD subjects underwent two human laboratory cocaine self-administration test sessions following an acute 3 -h pre-treatment with exenatide (5 mcg; subcutaneously) or placebo. Primary outcomes consisted of infusions of cocaine and visual analog scale self-ratings of euphoria and wanting cocaine. Secondary outcomes consisted of pertinent hormone levels (GLP-1, insulin, and amylin). Thirteen individuals completed the study. Acute pretreatment with exenatide versus placebo did not change cocaine infusions (8.5 ± 1.2 vs. 9.1 ± 1.2; p = 0.39), self-reported euphoria (4.4 ± 0.8 vs. 4.1 ± 0.8; p = 0.21), or wanting of cocaine (5.6 ± 0.9 vs. 5.4 ± 0.9; p = 0.46). Exenatide vs. placebo reduced levels of GLP-1 (p = 0.03) and insulin (p = 0.02). Self-administered cocaine also reduced levels of GLP-1 (p < 0.0001), insulin (p < 0.0001), and amylin (p < 0.0001). We did not find evidence that low dose exenatide alters cocaine self-administration or the subjective effects of cocaine in people with CUD. Limitations such as single acute rather than chronic pre-treatment, as well as evaluation of only one dose, preclude drawing firm conclusions about the efficacy of exenatide. Exenatide and cocaine independently reduced levels of GLP-1 and insulin, while cocaine also reduced levels of amylin.